Molecular analysis of the GNPTAB and GNPTG genes in 13 patients with mucolipidosis type II or type III - identification of eight novel mutations - Encarnação, Marisa (2012)
Mucolipidosis II (ML II) and mucolipidosis III (ML III) are diseases in which the activity of the uridine diphosphate (UDP)-N-acetylglucosamine:lysosomal enzyme N-acetylglucosamine-1-phosphotransferase (GlcNAc-phosphotransferase) is absent or reduced, respectively. In the absence of mannose phosphorylation, trafficking of lysosomal hydrolases to the lysosome is impaired. In these diseases, mistargeted lysosomal hydrolases are secreted into the blood, resulting in lysosomal deficiency of many hydrolases and a storage-disease phenotype. GlcNAc-phosphotransferase is a multimeric transmembrane enzyme composed of three subunits (alpha, beta and gamma) encoded by two genes -GNPTAB and GNPTG. Defects in GNPTAB result in ML II and III whereas mutations in GNPTG were only found in ML III patients. We have performed a molecular analysis of the GNPTAB and GNPTG genes in 13 mucolipidosis II and III patients (10 Portuguese, one Finnish, one Spanish of Arab origin and one Indian). Mutations were identified by the study of both cDNA and gDNA. The GNPTAB and GNPTG mRNA expressions were determined by quantitative reverse transcriptase polymerase chain reaction (qRT-PCR). The study led to the identification of 11 different mutations. Eight of these mutations are novel, six in the GNPTAB gene [c.121delG (V41FfsX42), c.440delC (A147AfsX5), c.2249_50insA (N750KfsX8), c.242G>T (W81L), c.1208T>C (I403T) and c.1999G>T (p.E667X)] and two in the GNPTG gene [c.610-1G>T and c.639delT (F213LfsX7)]. With regard to the mRNA expression studies, the values obtained by qRT-PCR indicate the possible existence of feedback regulation mechanisms between alpha/beta and the gamma subunits.